Improving the physical properties of fish gelatin by high hydrostatic pressure (HHP) and ultrasonication (US). (12th January 2020) - Sezer, Purlen; Okur, Ilhami; Oztop, Mecit Halil; Alpas, Hami
Summary: In this study, it was aimed to improve the physical properties of fish gelatin by using high hydrostatic pressure (HHP) and ultrasonication (US). Gelatin solutions were exposed to different pressures and ultrasonication separately and gelled afterwards. The physicochemical measurements based on gel strength, turbidity and rheology experiments showed that HHP treatment on fish and bovine gelatin stabilized the gelatin network by organising the structure and reducing the free volume. Both processing methods (HHP and US) increased the gel strength significantly ( P  < 0.05) compared with non‐treated samples. Fourier‐transform infrared spectroscopy (FTIR) results indicated that conformations of amino acids changed after the treatments. Furthermore, US treatment was shown to destroy the gelatin network, change the gelation mechanism and decreased the degree of aggregation. Both treatments improved the gel characteristics as gel strength, gelling and melting temperatures of the fish gelatin. At the end, the best combination for fish gelatin among HHP and US treatments was found as 400 MPa–10 °C–15 min pressurisation. Abstract : Physical properties of fish gelatin were improved by using High Hydrostatic Pressure (HHP) and ultrasonication (US). Both processing methods (HHP and US) increased the gel strength significantly compared to non‐treated samples.